The Position of Muslim Inheritors in Incestuous Marriages from the Perspective of Islamic Family Law Philosophy - Dedi Supriadi; Idzam Fautanu; Usep Saefulloh; Gilang Rizki Aji Putra (JURNAL ILMU SYARIAH, 2025)
Islamic law that is of particular concern in positive law is the law of marriage. A marriage carried out by a person will give rise to inheritance laws for their children if the marriage is carried out with a valid contract and is justified by Islamic law. Inheritance law itself is a law that regulates the transfer of wealth from a deceased person to a living person because the existence of these rules is justified by Islamic law, although in practice this inheritance can be seen from several angles, because of marriage, because of kinship and so on, the question is how is the position of children in an incestuous marriage, and whether the status of the child's inheritance incest is the same as the position of the Muslim inheritance in an incestuous marriage. That the position of children in an incestuous marriage is the same as the position of children in a legal marriage, because an incestuous marriage itself is a legal marriage as long as there is no annulment, and when an annulment occurs against a marriage, it does not apply retroactively to the status of the child's position, because the annulment of a marriage does not immediately result in the annulment of a child who has been born, an incestuous marriage has been in accordance with the provisions at the beginning. It can be understood that the distribution of inheritance to children of incestuous marriages is the same as the distribution of inheritance to legitimate children, because incestuous children are legitimate children and not children born from adultery or interfaith marriages, so that the position of incestuous children is the same as the position of legitimate children in receiving inheritance and can inherit from both parents, both from the mother and father. Keywords: Marriage; Heirs; Philosophy